2019
DOI: 10.1021/acsnano.9b04715
|View full text |Cite
|
Sign up to set email alerts
|

Switching the Spin on a Ni Trimer within a Metal–Organic Motif by Controlling the On-Top Bromine Atom

Abstract: Controlling the spin of metal atoms embedded in molecular systems is a key step towards the realization of molecular electronics and spintronics. Many efforts have been devoted to explore the influencing factors dictating the survival or quenching of a magnetic moment in a metal-organic molecule, and among others, the spin control by axial ligand attachments is most promising. Herein, from the interplay of highresolution STM imaging/manipulation and STS measurements together with DFT calculations, we successfu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 66 publications
0
16
0
Order By: Relevance
“…Experimentally, it has been shown that the Kondo spin-screening can be switched on and off by chemical doping. [23][24][25] A reduced barrier height usually means enhanced kinetics. Thus, with T s being much lower than the temperature of reactant species (T r ), the accelerated heterogeneous reaction is reminiscent of skating on an ice rink.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimentally, it has been shown that the Kondo spin-screening can be switched on and off by chemical doping. [23][24][25] A reduced barrier height usually means enhanced kinetics. Thus, with T s being much lower than the temperature of reactant species (T r ), the accelerated heterogeneous reaction is reminiscent of skating on an ice rink.…”
Section: Resultsmentioning
confidence: 99%
“…21 Extensive works have been carried out to fine-tune the strength of Kondo screening by adjusting the microenvironment of the TM adatom. [22][23][24][25] However, the thermochemical change associated with the Kondo spin-screening phenomenon and its implication to the chemical reactions catalyzed by the TM adatom are largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally, it has been shown that the Kondo spin-screening can be switched on and off by chemical doping. [31][32][33] A reduced barrier height usually means enhanced kinetics. Thus, the heterogeneous reaction could be effectively accelerated by tuning T s to be much lower than the temperature of reactant species (T r ), the accelerated heterogeneous reaction is reminiscent of skating on an ice rink.…”
Section: Fsmentioning
confidence: 99%
“…29 Extensive works have been carried out to fine-tune the strength of Kondo screening by adjusting the microenvironment of the TM adatom. [30][31][32][33][34] However, the thermochemical change associated with the antiferromagnetic Kondo spin-screening phenomenon and its implication to the chemical reactions catalyzed by the TM adatom are largely unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…Physically, the Kondo states originate from the screening of the local spin of d electrons on the TM atom by the spins of itinerant electrons in the metal substrate. Recently, the precise control and tuning of Kondo states have become a focus of experimental efforts [10][11][12][13][14][15][16][17] . However, it is generally observed that the Kondo features vary greatly with the local chemical environment surrounding the TM atom, such as the coordinating ligands, the chemical dopants, the metal substrate, etc.…”
mentioning
confidence: 99%